Feedback regulation between atypical E2Fs and APC/CCdh1 coordinates cell cycle progression. (5th February 2016) - Boekhout, Michiel; Yuan, Ruixue; Wondergem, Annelotte P; Segeren, Hendrika A; van Liere, Elsbeth A; Awol, Nesibu; Jansen, Imke; Wolthuis, Rob MF; de Bruin, Alain; Westendorp, Bart
Abstract: E2F transcription factors control the oscillating expression pattern of multiple target genes during the cell cycle. Activator E2Fs, E2F1–3, induce an upswing of E2F targets, which is essential for the G1‐to‐S phase transition, whereas atypical E2Fs, E2F7 and E2F8, mediate a downswing of the same targets during late S, G2, and M phases. Expression of atypical E2Fs is induced by E2F1–3, but it is unknown how atypical E2Fs are inactivated in a timely manner. Here, we demonstrate that E2F7 and E2F8 are substrates of the anaphase‐promoting complex/cyclosome (APC/C). Removal of CDH1, or mutating the CDH1‐interacting KEN boxes, stabilized E2F7/8 from anaphase onwards and during G1. Expressing KEN mutant E2F7 during G1 impairs S phase entry and eventually results in cell death. Furthermore, we show that E2F8, but not E2F7, interacts also with APC/C C dc20 . Importantly, atypical E2Fs can activate APC/C C dh1 by repressing its inhibitors cyclin A, cyclin E, and Emi1. In conclusion, we discovered a feedback loop between atypical E2Fs and APC/C C dh1, which ensures balanced expression of cell cycle genes and normal cell cycle progression. Synopsis: This study shows that the APC/C targets E2F7 and E2F8 for degradation, while these atypical E2Fs in their turn activate the APC/C by repressing its main inhibitors. Disturbing this feedback alters the oscillating expression of critical S phase genes and perturbs DNA replication. The transcription repressors E2F7 and E2F8 are targeted for proteasomal degradation by APC/C C dh1 during mitotic exit and G1 phase. Expressing KEN mutant stable versions of E2F7/8 in G1 leads to unscheduled repression of cell cycle genes, perturbed DNA replication, and cell death. E2F7 and E2F8 can activate APC/C C dh1 by repressing its main inhibitors Emi1 and the cyclins A and E. Interdependent activity of E2F7, E2F8, and APC/C balances expression of partially overlapping sets of key cell cycle genes. Abstract : This study shows that the APC/C targets E2F7 and E2F8 for degradation, while these atypical E2Fs in their turn activate the APC/C by repressing its main inhibitors. Disturbing this feedback alters the oscillating expression of critical S phase genes and perturbs DNA replication.